Laser Therapy in Lumbar Disc Surgery : A Narrative Review - Hosseini, Behnam; Allameh, Farzad (Journal of Lasers in Medical Sciences, 2020)
Introduction: Low back pain is one of the most chronic debilitating conditions involving considerable loss of cash, work, and quality time. Lasers are utilized in different fields of drugs, providing unique advantages. They are useful and advantageous in treating lumbar disc disease. In this research, an attempt is made to examine the role and importance of different lasers in lumbar disc surgeries. Methods: We conducted studies about laser therapy in lumbar disc surgery. Our primary search began with reviewing English-language citations from PubMed and Scopus between 1990 and 2019 using the keywords: (laser therapy) OR (lumbar disc AND disc surgery). The initial search yielded 97 articles. However, about 49 articles were selected and used in the present study. Results: Based on the present study, it can be found that there are several methods of using lasers to treat lumbar disc surgery. These methods all have their strengths and weaknesses. Conclusion: The development of laser lumbar disc surgery can be very helpful due to the reduction of surgical risks and the length of the patients’ hospital stay. However, the choice of method used for this type of surgery should be made according to the patient’s condition and based on the opinion of the treating physician.